EDUCATIONAL INTERVENTION AND ITS EFFECT ON HEALTH MANAGEMENT PRACTICES IN ADULTS WITH DIABETES - CELINE MATHEW C. (The Journal of Research ANGRAU, 2026)
The present study aimed to assess the effectiveness of an educational intervention on dietary practices, lifestyle behaviors and glycemic control among diabetic patients. A structured educational programme supported by a computer-based software package was implemented among 33 diabetic patients in the experimental group, while 35 patients served as controls. The intervention emphasized dietary modification, physical activity, medical monitoring and risk factor awareness. Results indicated that 12 out of 15 recommended dietary practices were significantly adopted by the experimental group following intervention. Post-intervention, there was a marked increase in the intake of green leafy vegetables, other vegetables, and fruits, along with a reduction in the consumption of cereals, fats and fleshy foods. Significant improvements were also observed in health management behaviors, including daily exercise, periodic blood glucose monitoring, and regular physician visits (P<0.01). Glycemic control improved substantially, as evidenced by a reduction in mean fasting plasma glucose from 172.21±47.49 mg/dl to 127.03±1.15 mg/dl and HbA1c from 9.53±1.64% to 7.50±0.99% (P<0.01). The study demonstrates that educational intervention is an effective strategy for improving dietary practices, lifestyle behaviors, and glycemic control among diabetic patients.